Building Employee Performance Through Sharia Work Culture And Work Motivation At Sharia Hotels In Pekanbaru - Jhonni Ardan Mardan; Saiful Anuar; Muhammad Ali Aqsa (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (ADPEBI), 2026)
This research investigated the influence of Sharia Work Culture and Work Motivation on Employee Performance within Sharia Hotels located in Pekanbaru. A quantitative methodology with an explanatory design was employed. The target population consisted of employees from several Sharia Hotels in Pekanbaru, encompassing both operational and administrative divisions. Through purposive sampling, 150 respondents who had worked for a minimum of one year and participated actively in daily hotel operations were selected. Data collection utilized a five-point Likert scale questionnaire, followed by analysis using JASP software. Classical assumption tests normality (Shapiro-Wilk), heteroscedasticity (Glejser), and multicollinearity (VIF) were performed prior to conducting simple and multiple linear regression analyses. The findings revealed that Sharia Work Culture positively and significantly influenced Employee Performance (B = 0.662; p < 0.001; R² = 0.438). Similarly, Work Motivation demonstrated a positive and significant effect on Employee Performance (B = 0.614; p < 0.001; R² = 0.377). When examined simultaneously, both variables collectively explained 61.2% of the variance in Employee Performance, with a significant combined effect (p < 0.001). These results imply that reinforcing Islamic work principles and enhancing motivational levels can substantially improve employee productivity and service quality in Sharia Hotels. This research offers practical insights for hotel management and enriches the existing literature on Islamic-based human resource management practices.